2012
DOI: 10.4238/2012.june.29.4
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone receptor splicing variants in bovine Leydig cells

Abstract: ABSTRACT. The luteinizing hormone receptor (LHR) plays a key role in testosterone production through its interaction with the gonadotropins, LH and chorionic gonadotropin. We examined the LHR splicing pattern in bovine Leydig cells; LH-induced expression of eight cloned splicing variants was detected by real-time PCR. Luteinizing hormone applied to cultured Leydig cells resulted in expression of full-length LHR and the A and B isoforms, as well as secretion of testosterone, which first increased, then declined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…In addition, Leydig cells that between seminiferous tubules produce growth factors and secrete testosterone. A previous study has shown that LHR plays a key role in testosterone production and eight splicing variants of LHR gene are detected in bovine Leydig cells [105]. The androgenic stimulation of peritubular myoid cells around seminiferous tubules is also essential for normal germ cell development [106].…”
Section: The Communication Between Sertoli-sertoli Cell Andmentioning
confidence: 99%
“…In addition, Leydig cells that between seminiferous tubules produce growth factors and secrete testosterone. A previous study has shown that LHR plays a key role in testosterone production and eight splicing variants of LHR gene are detected in bovine Leydig cells [105]. The androgenic stimulation of peritubular myoid cells around seminiferous tubules is also essential for normal germ cell development [106].…”
Section: The Communication Between Sertoli-sertoli Cell Andmentioning
confidence: 99%
“…(Genbank 2020). Este gen se expresa en las gónadas junto con el receptor de la FSH (FSHR), mientras que receptor el de la GnRH lo hace en la hipófisis anterior, está sujeto a corte y empalme alternativo (splicing alternativo), dando origen a diferentes variantes del mRNA del gen (Ma et al, 2012); en bovinos se han reportado variantes que carecen del exón 10 , deleción parcial del exón 11 (Robert et al, 2003;Nogueira et al, 2007) y del exón 3 (Nogueira et al, 2007).…”
unclassified
“…The genetic diversity in crossbred beef cows demonstrates that ILSTS002 and BMS3004 are associated with the luteinizing hormone-β (LHβ) gene on BTA18 that is associated with reproductive performance (SILVEIRA et al, 2013). In addition, receptors for luteinizing hormone (LHR) and follicle stimulating hormone (FSHR) genes located at BTA11 are also involved in the regulation of several essential reproductive processes occurring at the gonadal level (CHENG, 1975;MA et al, 2012).…”
Section: Introductionmentioning
confidence: 99%